The Agromyzidae (Diptera) of Greenland - Griffiths, Graham C. D. (Meddelelser om Grønland, 1966)
1. Nine species of Agromyzidae (Diptera) are recorded from Greenland, of which two are described as new. The new species are Cerodontha (Dizygomyza) thulensis, described from Thule in the Northwest, and Phytomyza vibeana, a species closely related to the holarctic P. ranunculi (SCHRANK}, described from Upernavik in Northwest Greenland and Hekla Havn in Continental East Greenland. 2. The following three species are considered to have reached Greenland through Iceland over a land-bridge from Europe during an interglacial period: Phytomyza opacella HENDEL, Phytomyza ranunculi (SCHRANK) and Phytomyza varipes MACQUART. 3. Four species are considered to represent a Nearctic element in the fauna, of which two are considered to be higharctic species which have reached Northwest Greenland from Ellesmere Island. These are: Cerodontha (Dizygomyza) thulensis sp. nov. and Napomyza parvicella (COQUILLET). The following two species are widespread in Greenland, and their route of arrival is not clear: Phytoliriomyza arctica (LUNDBECK) and Phytomyza fuscula ZETTERSTEDT. 4. The origin of the remaining two species - Cerodontha (Dizygomyza) lindrothi GRIFFITHS and Phytomyza vibeana sp. nov. - is not clear. The former species occurs also in Iceland. The latter may occur in central Europe, but confirmation of this is needed.